2020
DOI: 10.1002/jcla.23475
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of peripheral hematologic markers for coronavirus disease 2019 (COVID‐19): A multicenter, cross‐sectional study

Abstract: Background To determine the diagnostic value of hematologic markers for coronavirus disease 2019 (COVID‐19) and explore their relationship with disease severity. Methods Subjects included 190 COVID‐19 patients, 190 healthy subjects, and 105 influenza pneumonia (IP) patients. COVID‐19 patients were divided into the ARDS and non‐ARDS groups. Routine blood examination, biochemistry indicator, days in hospital, body temperature, pneumonia severity index (PSI), CURB‐65, and MuLBSTA were recorded. Correlations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 34 publications
13
125
0
6
Order By: Relevance
“…Further analysis revealed that CD3+, CD8+, total lymphocytes, platelets, and basophils in patients older than 50 were significantly lower than in patients younger than 50 ( P = P = .049, .018, .019, .010, and .039, respectively), while neutrophils, NLR, CRP level, and RBC RDW in patients older than 50 were significantly higher than in patients younger than 50 ( P = .0191, .015, .009, and .010, respectively) (Table 4). These results were similar to previous reports 14,28,29,38‐41 . The reduction of T‐cell subsets and the high CD4+/CD8+ T‐cell ratio are associated with disease severity; older‐aged cases tend to be more severe; thus, more lymphocytes would be consumed or severely impaired in the immune reaction.…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis revealed that CD3+, CD8+, total lymphocytes, platelets, and basophils in patients older than 50 were significantly lower than in patients younger than 50 ( P = P = .049, .018, .019, .010, and .039, respectively), while neutrophils, NLR, CRP level, and RBC RDW in patients older than 50 were significantly higher than in patients younger than 50 ( P = .0191, .015, .009, and .010, respectively) (Table 4). These results were similar to previous reports 14,28,29,38‐41 . The reduction of T‐cell subsets and the high CD4+/CD8+ T‐cell ratio are associated with disease severity; older‐aged cases tend to be more severe; thus, more lymphocytes would be consumed or severely impaired in the immune reaction.…”
Section: Discussionsupporting
confidence: 91%
“…The previous study has noticed the differences of lymphocytes and neutrophils between mild and sever patients 10,20‐22 . Also the higher neutrophils count than healthy people were found in COVID‐19 patients 23 . In our study, a clear reduction of lymphocytes and increase of neutrophils which was more intense than in mild group were observed in severe patients.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, patients with SP developed tended to have higher MPR levels than mild patients in the early stage after admission. Recent studies indicated that monocyte‐to‐lymphocyte ratio could be used to differentiate COVID‐19 patients from healthy subjects and neutrophil to lymphocyte ratio might be a reliable marker to assess the severity of COVID‐19 18 . These suggested that the dynamic change of hemocytes was of great clinical significance and became a research hotspot.…”
Section: Discussionmentioning
confidence: 99%